Ask your own question, for FREE!
Mathematics
OpenStudy (anonymous):

2x+4y=-6 x-3y=-7

7 years ago
OpenStudy (anonymous):

what do you need to do?

7 years ago
OpenStudy (anonymous):

Substitution

7 years ago
OpenStudy (anonymous):

okay here we go :)

7 years ago
OpenStudy (anonymous):

x=3y-7 2(3y-7)+4y=-6 -14+6y+4y=-6 10y=8 y=0.8 x=3(0.8)-7 x=2.4-7 x=-4.6

7 years ago
OpenStudy (anonymous):

Thanks. I'm going to take a look at this so I can see what you did

7 years ago
OpenStudy (anonymous):

ok: 2x+4y=-6 2x=-6-4y ( by transposing 4y to RHS ) 2x/2=(-6-4y)/2 x=(-6-4y)/2 NOW PUTTING THE VALUE OF x in the equation no. 2 : x-3y=-7 (-6-4y)/2-3y=-7 (-6-4y-6y)/2=-7 -12y-4=-14 transposing -4 to RHS -12y=-14+4 -12y=-10 y=-10/-12 y=5/6

7 years ago
Can't find your answer? Make a FREE account and ask your own question, OR you can help others and earn volunteer hours!